Design, synthesis and biological evaluation of CDC20 inhibitors for treatment of triple-negative breast cancer - Zhao, Shi-Fang; Leng, Jia-Fu; Xie, Shan-Shan; Zhu, Li-Qiao; Zhang, Meng-Yu; Kong, Ling-Yi; Yin, Yong (European journal of medicinal chemistry, 2024)
The involvement of CDC20 in promoting tumor growth in different types of human cancers and it disturbs the process of cell division and impedes tumor proliferation. In this work, a novel of Apcin derivatives targeting CDC20 were designed and synthesized to evaluate for their biological activities. The inhibitory effect on the proliferation of four human tumor cell lines (MCF-7, MDA-MB-231, MDA-MB-468 and A549) was observed. Among them, compound E1 exhibited the strongest inhibitory effect on the proliferation of MDA-MB-231 cells with an IC50 value of 1.43 μM, which was significantly superior to that of Apcin. Further biological studies demonstrated that compound E1 inhibited cancer cell migration and colony formation. Furthermore, compound E1 specifically targeted CDC20 and exhibited a higher binding affinity to CDC20 compared to that of Apcin, thereby inducing cell cycle arrest in the G2/M phase of cancer cells. Moreover, it has been observed that compound E1 induces autophagy in cancer cells. In 4T1 Xenograft Models compound E1 exhibited the potential antitumor activity without obvious toxicity. These findings suggest that E1 could be regarded as a CDC20 inhibitor deserved further investigation. [Display omitted] •The compounds were designed as potential inhibitors for CDC20 based on Apcin.•All derivatives were tested for antiproliferative activities against cell lines.•Compound E1 has been proven to have in vivo antiproliferative activity.•Discovery of autophagy as a pathway for cell death in compound E1.